2017
DOI: 10.1111/jav.01514
|View full text |Cite
|
Sign up to set email alerts
|

Uropygial gland volume and malaria infection are related to survival in migratory house martins

Abstract: Pathogens such as bacteria, fungi and malaria and related haemosporidians provoke negative effects on the fitness of their hosts. Animals have developed a range of defensive mechanisms to resist or eliminate these parasitic infections and their negative fitness costs. The uropygial gland secretion has been proposed to act as defensive barrier of skin and plumage in the fight against bacteria and fungi, and may prevent birds from acquiring haemosporidian infections. Thus, the secretion of uropygial glands of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
(55 reference statements)
0
9
0
1
Order By: Relevance
“…Blood parasite pathogenic potential can negatively affect wild bird's survival probability and consequently can also affect population dynamics [1][2][3][4]. By extension, parasite infections can have conservation impacts, particularly for small populations or declining bird species [3].…”
Section: Introductionmentioning
confidence: 99%
“…Blood parasite pathogenic potential can negatively affect wild bird's survival probability and consequently can also affect population dynamics [1][2][3][4]. By extension, parasite infections can have conservation impacts, particularly for small populations or declining bird species [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the cross-sectional design of the current study does not enable to demonstrate directly the absence of senescence in preen gland diameter, we suggest that monotonous increase of the preen gland size with age can be best explained by selective disappearance of the birds with smaller preen glands (and thus less capable of maintaining plumage in prime condition) from the older age cohorts. Consistent with such a scenario, a recent study in house martins (Delichon urbica) showed that malaria-infected birds with larger uropygial glands were better able to survive to the next breeding season, while infected birds with small uropygial glands were not (Magallanes et al 2017).…”
Section: Discussionmentioning
confidence: 70%
“…The size of the uropygial gland is positively related to the amount of secretions produced for a variety of species (Elder 1954;Møller et al 2010;Pap et al 2010) as the gland is made up of tubules where secretion of the substances occur (Jacob and Ziswiler 1982), and secretions are hypothesized to have antiparasitic substances (Moreno-Rueda 2017). Hence, selection for defence through uropygial gland secretions could be an important factor for fitness components such as reproductive success (Whittaker et al 2013) and survival (Merino et al 2000;Møller et al 2010;Magallanes et al 2017).…”
Section: Discussionmentioning
confidence: 99%